Navigating Legitimacy and Authority: The International Tribunal for the Law of the Sea Provisional Measures in Ukraine v. Russia - Khansa, Hanif Ardiningrum (Mimbar Hukum, 2025)
Abstract International maritime disputes involving geopolitical tensions test the legitimacy and authority of tribunals like the International Tribunal for the Law of the Sea (ITLOS). This article examines ITLOS’ provisional measures order in Ukraine v. Russia (2019) to assess how the Tribunal balances procedural fairness with enforcement challenges in politically charged disputes. Employing qualitative legal analysis, the study dissects ITLOS’ reliance on state consent and procedural integrity as pillars of its normative legitimacy, while evaluating its de facto authority through state participation and compliance. The article argues that ITLOS’ strict adherence to UNCLOS provisions reinforces its normative legitimacy, yet gaps in enforcement–exemplified by Russia’s partial compliance–reveal the limits of its authority in high-stakes conflicts. By contextualizing the case within broader debates on international adjudication, the analysis demonstrates how ITLOS’ procedural rigor mitigates non-participation risks but struggles to overcome power asymmetries. The study concludes with pragmatic reforms, including clarified jurisdictional guidelines, advisory opinions, and collaborations, to bolster ITLOS’ role in maritime dispute resolution. These findings illuminate the evolving challenges faced by international courts in reconciling legal principles with geopolitical realities. Abstrak Sengketa maritim yang melibatkan ketegangan geopolitik menguji legitimasi dan otoritas lembaga peradilan seperti Pengadilan Internasional untuk Hukum Laut atau the International Tribunal for the Law of the Sea (ITLOS). Artikel ini menganalisis tindakan sementara ITLOS dalam Ukraina v. Russia (2019) untuk menilai bagaimana Pengadilan menyeimbangkan keadilan prosedural dengan tantangan penegakan hukum dalam sengketa politis. Melalui analisis hukum kualitatif, studi ini mengkaji ketergantungan ITLOS pada persetujuan negara dan integritas prosedural sebagai pilar legitimasi normatif, sekaligus mengevaluasi otoritas de-facto-nya melalui partisipasi dan kepatuhan negara. Artikel ini berargumen bahwa kepatuhan ITLOS pada UNCLOS memperkuat legitimasi normatifnya, tetapi celah penegakan–ditunjukkan oleh kepatuhan parsial Rusia–mengungkap batasan otoritasnya dalam konflik berisiko tinggi. Dengan mengkontekstualkan kasus ini dalam debat peradilan internasional, analisis menunjukkan bahwa ketelitian prosedural ITLOS mengurangi risiko ketidakhadiran pihak, namun belum mampu mengatasi asimetri kekuasaan. Studi ini merekomendasikan reformasi pragmatis, termasuk panduan yang mengklarifikasi yurisdiksi, pandangan hukum, dan kerjasama, untuk memperkuat peran ITLOS. Temuan ini menyoroti tantangan yang dihadapi pengadilan internasional dalam memadukan prinsip hukum dengan realitas geopolitik.